Determinants of Labor Absorption in the MSME Sector in Regencies And Cities Of West Java Province - Lestari, Setia; Bariyah, Nurul; Jamaliah; Yanto; Wahyudi (Jurnal Ilmu Ekonomi Terapan, 2025)
This study aims This study aims to examine how labor absorption in the Micro, Small, and Medium Enterprises (MSME) sector in West Java Province is influenced by Gross Regional Domestic Product (GRDP), Average Years of Schooling (AYS), and the Regency/City Minimum Wage (RCMW) between 2018 and 2022. A multiple regression analysis was employed as the quantitative method of analysis in this research.The findings reveal that the RCMW significantly enhances labor absorption in the MSME sector. Although some MSMEs face challenges in adjusting to the rising wage costs, the increase in minimum wages ultimately benefits workers’ welfare and makes the MSME sector more attractive to employers. Moreover, AYS also has a significant positive impact on labor absorption. Higher education levels among the workforce contribute to improved productivity and enable MSMEs to expand their staff capacity.In contrast, GRDP demonstrates a significant negative impact on labor absorption in the MSME sector. The growth in regional income, predominantly driven by large-scale industrial sectors, tends to favor capital-intensive industries over labor-intensive MSMEs.This study underscores the importance of inclusive policies to support MSMEs. These policies may include adjusting minimum wages in alignment with the region’s economic capacity, expanding access to education and training programs, and enhancing MSMEs’ capacity development. In doing so, the MSME sector is expected to grow sustainably, increase labor absorption, and make a substantial contribution to the economy of West Java Province.